Prevalence of Inflammatory Backache and Radiographic Axial Spondyloarthritis Among Patients with Musculoskeletal Backache in Outdoor Patients of Rheumatology Department at PIMS Hospital - Gulelala; Rasheed, Uzma; Zammurrad, Shazia; Pasha, Taha Mohammad Usman; Khan, Muhammad Sufyan; Mansoor, Sadia (Pakistan Armed Forces Medical Journal, 2026)
Objective: To assess inflammatory back ache and radiographic axial spondylarthritis among patients with musculoskeletal backache in a single-center sample from Pakistan. Study Design: Analytical cross-sectional study. Place and Duration of Study: Department of Rheumatology, Pakistan Institute of Medical Sciences (PIMS), Islamabad, Pakistan, from Apr to Sep 2023. Methodology: Patients visiting the Rheumatology outpatient department (OPD), with backache, were assessed for inflammatory backache using the Assessment of Spondyloarthritis International Society (ASAS) criteria to determine the occurrence of spondyloarthritis. Pain levels were recorded on a Visual Analogue Scale (VAS) and sacroiliitis on imaging was also recorded as per the modified New York criteria. Results: Out of a sample of 74 patients, 48(64.90%) were diagnosed as having inflammatory backache. Patients with inflammatory backache had higher pain levels (median = 6.00, IQR = 1.00 VAS) and more frequently reported higher C-reactive protein (CRP) levels (n=12, 92.30%) and greater pain levels, as compared to those without inflammatory backache (median = 5.00, IQR = 2.00 VAS; higher CRP n = 1, 7.70%). Conclusion: Inflammatory backache was highly frequent among patients with backache and associated clinical features were more frequently present among patients with inflammatory backache.